Reduced Invasiveness of Common Ragweed (Ambrosia artemisiifolia) Using Low-Dose Herbicide Treatments for High-Efficiency and Eco-Friendly Control - Hanyue Wang; Tong Liu; Wenxuan Zhao; Xuelian Liu; Mingming Sun; Pei Su; Jun Wen (Frontiers in Plant Science, 2022)
Common ragweed (Ambrosia artemisiifolia) is an invasive annual weed that invades heavily disturbed habitats and natural habitats less disturbed by human activities with native plant species in need of protection. Achieving effective control of A. artemisiifolia for the protection of native organisms and the local ecological environment is an ongoing challenge. Based on the growth and development characteristics of A. artemisiifolia, we examined the effectiveness of herbicides in controlling this species and the optimal time for application in the field with the aim of reducing herbicide dosage. Additionally, we analyzed whether the efficiency of low-dose applications for controlling this species might improve with increasing native plant species richness. Our findings indicate that aminopyralid (33 g ai ha−1) was the most suitable herbicide for chemical control of A. artemisiifolia, with optimum application time being during vegetative growth (BBCH 32–35). Application of aminopyralid was found to kill approximately 52% of A. artemisiifolia plants, and more than 75% of the surviving plants did not bloom, thereby reducing seed yield of the population by more than 90%. Compared with the application of high-dose herbicide, the phytotoxicity of aminopyralid to native plants at the applied dose was substantially reduced. After 2 years of application, the relative coverage of A. artemisiifolia significantly decreased, with few plants remaining, whereas the relative coverage of native plants more than doubled, representing an eco-friendly control. Further, there was an increase in the A. artemisiifolia control rate in the plant community with higher native plant species richness at the same herbicide rates and a reduction in seed yield of A. artemisiifolia. Our findings help toward developing control measures to reduce the invasiveness of A. artemisiifolia with low-dose herbicides meanwhile protecting native plants, and then using the species richness of native plant communities to indirectly promote the effectiveness of low-dose herbicide application.